Pengarusutamaan Moderasi Beragama di Sekolah Dasar - Hisny Fajrussalam; Iskandar, Sofyan; Mustikaati, Wina; Sya'bani, Yahya Rafi; Anisah, Anisah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Community Service (PkM) is carried out in Edutama School Karawang. The problem faced by partners is the moral quality of children which is quite concerning. The problem is the current phenomenon of students having a tendency towards intolerant and radical attitudes which is quite worrying. Symptoms of intolerance and radicalism tend to be greater in religious issues than in ethnicity issues. Therefore, mainstreaming religious moderation needs to be carried out in educational institutions. This PkM aims to find alternatives to the problems faced by partners, namely the community. The method of implementing this PkM is carried out through 3 stages, namely: 1) preparation; 2) implementation; and 3) evaluation. The results or achievements of this PkM are: 1) The curriculum has an important role in education, especially in the teaching and learning process. 2), Educators, then how to prepare teachers who have professionalism in teaching by prioritizing the principles of washatiyah, the principle of justice, and the principle of nurturing. 3), Material, then to convey the values of religious moderation to students, as a teacher you need to first have an understanding of the concept of religious moderation and have applied it in everyday life.